Cyber-physical systems : solutions to pandemic challenges - Semwal, Tushar; Iqbal, Faiz (CRC Press, 2022)
A Cyber-Physical System (CPS) is an integration of cyber components with their physical counterparts. A cyber unit could be either a software or hardware. Physical components are those objects, which are governed by the law of physics. CPS have transformed how we interact with the physical world, ranging from sensing the environmental parameters to controlling a complex manufacturing industry. The current pandemic has had catastrophic implications people all across the world in terms of health and economy. This book presents the significance and practicality of CPS in a pandemic situation. It provides a strong foundation to the CPS while also incorporating the latest theoretical advances and practical applications to alleviate the state of a pandemic. The book covers ... Theoretical background and application-oriented overview of the different CPS models Impact of COVID-19 and similar pandemics on the engineering aspects of various industries and organisations Exciting and impactful CPS based solutions to the different pandemic situations Security and privacy in CPS when applied to critical and sensitive pandemic affected environment Describes the government-funded projects and work using CPS in real-world scenarios The book provides a unique and fresh exposure to CPS employed in a pandemic situation. It brings together researchers, practitioners, academics, experts, and industry professionals from around the world to share their knowledge and experience.